The importance of prevention programs to reduce bullying: A comparative study - Sainz, Vanesa; Martín-Moya, Beatriz (Frontiers in Psychology, 2023)
Bullying is a growing and increasingly worrying phenomenon. In recent years, a number of different bullying prevention programs have been implemented to create a more positive school environment. This paper offers a description of these prevention programs, focussing on the three most commonly implemented in schools: TEI, KiVa and Mediation Teams. A qualitative, descriptive and comparative analysis was made using semi-structured interviews with tutors, coordinators and experts at nine schools, three schools for each of the programs. The results show that these bullying prevention programs help raise awareness of this problem within the entire school community, improving the school environment and reducing conflict and instances of bullying. Overall, participating schools reported being highly satisfied with the results of these programs and it is therefore important to consider the mandatory implementation of bullying prevention programs in all schools.